Lack of association between COX-2 8473T>C polymorphism and breast cancer risk: a meta-analysis - Jiang, Jun; Quan, Xun-Feng; Zhang, Li; Shen, Li; Zhang, Ming-Xia; Ma, Hui-hui; Wang, Yi-Chun (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Results of recent published studies on the association between the COX-2 8473T>C polymorphism and the risk of breast cancer have often been conflicting. To make a more precise estimation of the potential relationship, a meta-analysis was performed. Material and methods: A total of seven case-control studies with 7,033 cases and 9,350 controls were included in the current meta-analysis through searching the databases of PubMed, Embase, and Cochrane Library (up to March 1st, 2013). The odds ratio (OR) and 95% confidence interval (95% CI) were calculated to assess the strength of the association. The meta-analysis was conducted in a fixed/random effect model. Results: We found no significant associations for all genetic models after all studies were pooled into the meta-analysis (for C vs. T: OR = 0.974, 95% CI: 0.906–1.047, p = 0.471; for CC vs. TT: OR = 0.957, 95% CI: 0.803–1.140, p = 0.62; for TC vs. TT: OR = 0.964, 95% CI: 0.881–1.055, p = 0.421; for CC + TC vs. TT: OR = 0.963, 95% CI: 0.880–1.053, p = 0.406; for CC vs. TT + TC: OR = 0.978, 95% CI: 0.831–1.15, p = 0.788). We also observed no obvious associations in the subgroup analyses by ethnicity (Caucasian) and source of controls (population based, PB) for all genetic models. Conclusions : Current evidence suggests that the COX-2 8473T>C polymorphism is not associated with breast cancer risk.